A comparative study of interface engineering with different hole transport materials for high-performance perovskite solar cells. (January 2020) - Haider, Syed Zulqarnain; Anwar, Hafeez; Jamil, Yasir; Shahid, Muhammad
Abstract: In recent years, perovskite solar cells (PSCs) are performing remarkably with efficiency more than 20%. Performance can further be improved by controlling charge transfer and recombination at electron transport material (ETM)/absorber and absorber/hole transport material (HTM) interfaces which ultimately define conduction band offset (CBO) and valence band offset (VBO). Therefore, it is worthwhile to investigate optimum band offset to get efficient PSCs. Spiro-MeOTAD is organic HTM commonly used in PSCs while CuI, CuSCN and Cu2 O are inorganic HTMs which may replace spiro-MeOTAD due to their low cost and stability. In this paper, device simulation approach is used to analyze the effect of CBO, VBO and interface defect density (Nt ) on the performance of PSCs for spiro-MeOTAD as organic HTM and its detailed comparison is made with Cu-based inorganic HTMs to get better insight about the best inorganic HTM. The device simulation shows that CuI has the best PCE of 22.69% when CBO and VBO is set to be +0.2 eV and 0 eV respectively at Nt of 1 × 10 15 cm −3 . The results indicate that Cu-based inorganic HTMs are efficient as well as stable HTMs and can be used towards commercializing the PSCs. Highlights: Comparative study of device engineering of perovskite solar cell with different organic and inorganic HTMs. Effect of CBO, VBO and Nt of interfaces on the performance of the devices is investigated. The PSC with CuI as HTM exhibits best PCE of 22.69%. This study shows useful inorganic HTMs alternate to traditional organic HTM. Performance of the PSCs strongly depends on the defect density and band offsets.